Harmonization between Islam and International Human Rights: a critical analysis - Haneef, Sayed Sikandar Shah (IIUM Press, 2016)
The issue as to whether Islam accommodates the notion of human rights as embodies in International law within its framework is a contested topic among the Muslim academia. This paper after reviewing various positions on the issue argues for methodological harmonization between the two within Islamic parameters and non-negotiable principles of Islamic view on humans and their rights.